A sound track to ecological crisis: tracing guitars all the way back to the tree. Issue 2 (May 2019) - Gibson, Chris
Abstract: Analyses of music and environment are proliferating, yet new conceptions are needed to make sense of growing ecological crisis in the Anthropocene. From an empirical project tracing guitars all the way back to the tree, I argue for deeper conceptual and empirical integration of music into the material and visceral processes that constitute ecological crisis itself. Musicians are not only inspired by environmental concerns for compositional or activist purposes. They are entangled in environmental crisis through material and embodied relations with ecosystems, especially via the musical instruments we depend upon. I foreground three 'more-than-musical' themes to make sense of unfurling forces: materiality, corporeality and volatility. Musical instruments are gateway objects that invite contemplation of material and corporal relations. Such relations bind together musicians and non-human others. Material and corporeal relations with increasingly threatened upstream forests, and endangered tree species, are being confronted and reconfigured. In the context of ecological crisis, guitars do much more than make pleasing acoustic sounds. Via guitars we co-generate, with non-human others, a sound track of crisis both melancholy and hopeful.